Analisis Aspek-Aspek Keberhasilan Pembelajaran di Indonesia: Ditinjau dari Studi Observasi - Siregar, Deasy Yunita; Khairani, Lutfi Putri; Sabilla, Sonia; Yusriani, Yusriani; Siahaan, Rizki Putri Jasmine (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The importance of this research lies in its contribution to the development of education policies, the formulation of more effective teaching strategies, and the guidance for education practitioners. With a better understanding of the factors influencing learning success, this research is expected to be a valuable guide in improving the quality of education in Indonesia to meet global demands and prepare future generations optimally. Observational analysis research is a research approach in which the researcher directly observes certain phenomena or events to gain a deeper understanding. In this context,